THE FUTURE OF PUBLIC HEALTHCARE MANAGEMENT: FROM THE BUREAUCRATIC MODEL TO THE SERVICE ECOSYSTEM LOGIC - Cahyadi, Rachmad; Fahrudda, Ansarul; Setiawan, Heri Cahyo Bagus; Mufidah, Eva (JURNAL EMA (Ekonomi Manajemen Akuntansi), 2025)
This article aims to explore the transformation of public healthcare management paradigms from a bureaucratic model to a service ecosystem logic. This conceptual approach critiques the traditional bureaucratic model that positions hospitals as administrative institutions and patients as passive service recipients. Through literature analysis and theoretical reflection, this study formulates a conceptual framework for hospital management based on a public value ecosystem. The findings suggest that implementing a service ecosystem logic requires reorienting hospitals’ roles as collaborative nodes connecting doctors, patients, communities, local governments, and private sectors in the co-creation of health value. The theoretical contribution of this article lies in reconceptualizing hospitals as collaborative ecosystems that sustainably generate public value. Practically, the study provides a new direction for Indonesia’s public healthcare management to develop adaptive, inclusive, and socially oriented service systems.